Curiosidades - Alvarado Vázquez, Marco A.; Salcedo Martínez, Sergio M.; Vargas López, Victor Ramón (Revista Planta, 2024)
Se presentan algunos datos curiosos sobre ciencia, vida cotidiana y naturaleza.